2015
DOI: 10.4103/0253-7176.155624
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Assessment in Obsessive-Compulsive Disorder

Abstract: Background:Neuropsychological deficits in obsessive-compulsive disorder (OCD) have been encouraged by brain imaging studies suggesting a putative fron to- striatial biological basis of the condition. Studies of neuropsychological functions in OCD have documented deficits in several cognitive domains, particularly with regard to visuospatial abilities, executive functioning, motor speed and memory. The Aim of the present study was to assess neuropsychological profile of patients with OCD. Objectives of the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 44 publications
1
5
1
Order By: Relevance
“…The fact that there were no significant differences between groups on other neuropsychological tests suggests that the neuropsychological functioning of OCD subjects can be altered upon the presence of emotional stimuli. These results add relevant information to the controversial findings on the neuropsychological performance of individuals with OCD (Abramovitch & Cooperman, 2015;Kohli et al, 2015). Lack of differences between groups in fear recall and fear renewal suggests that OCD in Puerto Ricans may not be characterized by difficulty in maintaining fear acquisition and extinction memories.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…The fact that there were no significant differences between groups on other neuropsychological tests suggests that the neuropsychological functioning of OCD subjects can be altered upon the presence of emotional stimuli. These results add relevant information to the controversial findings on the neuropsychological performance of individuals with OCD (Abramovitch & Cooperman, 2015;Kohli et al, 2015). Lack of differences between groups in fear recall and fear renewal suggests that OCD in Puerto Ricans may not be characterized by difficulty in maintaining fear acquisition and extinction memories.…”
Section: Discussionsupporting
confidence: 51%
“…Other studies have found deficiencies in tasks that require set-shifting (Tukel et al, 2012) and response inhibition in individuals with OCD (Pena-Garijo et al, 2010). However, Kohli et al (2015) assessed verbal intelligence, memory, perceptual and motor functions in OCD outpatients using tests, such as the Wisconsin Card Sorting Test (WCST) and the Bhatia Battery of Performance tests of Intelligence (BSS) and participants did not show impairments in any of the cognitive functions, compared to healthy controls. The controversial findings of neuropsychological functions in individuals with OCD enhance the need to assess these functions, especially in Puerto Ricans, given the lack of research in Latinos with OCD (Williams et al, 2010).…”
Section: Neuropsychology Of Ocdmentioning
confidence: 99%
“…On the TMT-B, the results seem to be inconsistent with some studies finding equal performances between OCD patients and healthy controls [13,19,20,25,34,35,51] while others do not [11,17,30,33]. With the WCST, there is far less inconsistencies, especially with regard to perseverative errors, with a pronounced trend towards poorer performance exhibited by OCD patients [8,11,[14][15][16]19,22,[34][35][36]40,44,45,51,[56][57][58][59][60][61]; even though some studies failed to report this difference [13,21,24,25,31,49,62,63] More recently, computerized tasks were developed to assess behavioral flexibility with more specificity and in a more controlled fashion. Indeed, even though they were designed to assess flexibility, the TMT-B and WCST are not specific to this cognitive dimension; other processes are involved such as attention, speed processing, motor speed, or working memory.…”
Section: Flexibilitymentioning
confidence: 99%
“…The literature is inconsistent concerning this dimension, with some studies showing an impairment [11,17,20,24,25,31,34,35,52•] while others do not [8,13,15,18,19,21,30,37,50,56,62,63]. shows that the slowdown characterizing OCD patients does not explain this impairment.…”
Section: Verbal Fluencymentioning
confidence: 99%
“…There are studies demonstrating the impairment in this function in patients with OCD (6,7,8,9). On the other hand, there are also studies published that conclude that there are no impairments of set-shifting in OCD (10,11,12,13). In 9 of the 19 studies examining fluency, which is another executive function, the OCD group displayed similar performance to healthy controls and in 7 of those studies, patients with OCD performed significantly poorer than healthy controls (14).…”
Section: Introductionmentioning
confidence: 99%